The Effects of Workload and Compensation on Turnover Intention With Burnout as An Intervening Variable Among Millennial Employees of PT. KGM - Erlinda Dwi Puspitasari; Slamet Riyadi; Abdul Halik (PT Inovasi Pratama Internasional, 2024)
Human resources are plentiful in Indonesia, yet many businesses still need to build up their HR departments. As competition for jobs becomes fiercer, businesses face new challenges including employee churn. This was done so that we could learn how burnout affects PT. KGM employees' willingness to leave their current jobs in relation to workload and pay. The sample size is representative, consisting of 208 PT. KGM staff members. Sixty-eight people were included in the sample. Interviews and questionnaires as methods of gathering information. SEM-PLS is used for data processing and analysis. In light of the data, it may be concluded that (1) workload significantly affects burnout. (2) There is no correlation between pay and job satisfaction or burnout. (3) there is no correlation between work load and a person's purpose to leave their current job. (4) There is no correlation between pay and desire to leave the company. (5) Burnout significantly affects intentions to leave a company. (6) Burnout mediates well since it has been shown that burnout and workload have a substantial impact on turnover intention. (7) There is no statistically significant mediation impact of burnout on the connection between pay and desire to leave the organization. The goal of PT KGM is to limit the number of workers who want to leave the company by improving working conditions and paying them a competitive wage.